Estudio de la autogestión del Cuerpo de Bomberos del cantón Montalvo del periodo 2020 - Cedeño Tinoco, Nora Abigail (2021)
The purpose of this case study is to analyze what are the economic income that the Montalvo Fire Department has for its economic and financial sustainability, such as the operating permit rates, urban and rustic properties (PUR) and the service fee. electricity, the same that should be charged until the end of the period for a correct self-management of economic resources and the proper development of the necessary activities and the acquisition of materials and / or equipment, achieving the purpose of the institution that is to serve the community in general in adverse or anthropic situations 24 hours a day. Where it was identified that the lack of general budgets is due to several factors, among which it is mentioned; maintain a correct organization within the institution, the use of adequate systems to control users to collect operating fees and the contribution by external entities such as the Autonomous Decentralized Municipal Government of the Cantón Montalvo (GADM) and the company CNEL (national electricity corporation).